2002
DOI: 10.1038/sj.leu.2402639
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD20-based therapy of B cell lymphoma: state of the art

Abstract: Over the last 5 years, studies applying the chimeric anti-CD20 MAb have renewed enthusiasm and triggered world-wide application of anti-CD20 MAb-based therapies in B cell non-Hodgkin's lymphoma (NHL). Native chimeric anti-CD20 and isotopelabeled murine anti-CD20 MAbs are currently employed with encouraging results as monotherapy or in combination with conventional chemotherapy and in consolidation of remission after treatments with curative intent (ie after/ in combination with high-dose chemotherapy and hemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 69 publications
0
31
0
2
Order By: Relevance
“…Tumors reached a maximal size of 250 AE 100 mm 3 . Prior to imaging, mice were anesthetized with a mixture of 18.75 mg/kg ketamine hydrochloride (Ketamine 1000 Ceva, Ceva) and 0.5 mg/kg medetomidine hydrochloride (Domitor, Pfizer).…”
Section: Animal Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“…Tumors reached a maximal size of 250 AE 100 mm 3 . Prior to imaging, mice were anesthetized with a mixture of 18.75 mg/kg ketamine hydrochloride (Ketamine 1000 Ceva, Ceva) and 0.5 mg/kg medetomidine hydrochloride (Domitor, Pfizer).…”
Section: Animal Modelsmentioning
confidence: 99%
“…99m Tc-sdAbs were separated from unbound ( 99m Tc(H 2 O) 3 (CO) 3 ) þ via NAP-5 size exclusion chromatography (SEC; Sephadex, GE Healthcare). The eluate was filtered and the radiochemical purity was evaluated by iTLC (iTLC-SG, Pall Corporation).…”
Section: Preparation Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Many studies have demonstrated that crosslinking of CD20 with mAbs can recruit immunological molecules that trigger strong cytotoxic effects, such as antibody-dependent cellular cytotoxicity (ADCC) and complement-dependent cytotoxicity (CDC). 10 Moreover, CD20 has very high expression levels in patients with B-cell lymphoma, and there is almost no free CD20 in serum to compete with binding of mAbs. 11,12 These characteristics make CD20 an excellent target for B-cell related disease therapy.…”
Section: Introductionmentioning
confidence: 99%